Analisis Kinerja Pegawai Ditinjau dari Pelatihan dan Pendidikan dan Pemberian Insentif - Cosmas cosmas; Sangkala Sangkala; Hasniati Hasniati (EKONOMI & SOSIAL, 2021)
Low performance can be caused by technical aspects such as lack of knowledge from an employee, high workload and lack of commensurate remuneration for high work volumes. The aim is to determine the role of training and education as well as the provision of incentives in improving employee performance. The method used is a qualitative method which is then presented in descriptive form. Training and education have a very big influence on improving employee performance at the Navigation District office because there are many employees who are placed in fields that are not in accordance with their fields of knowledge while the provision of incentives is also very influential on improving performance, this can be seen from the number of employees who have completed the right job targets. less time and errors in work. The provision of incentives greatly motivates employees at the Class III Navigation District office to work so that it is very influential on improving employee performance, this can be seen from the work targets that are always completed on time and errors can be minimized and this can be monitored through the performance appraisal application. and employee performance calculations